GSM-based notification system for electronic pigeon hole - Abd Wahab, Mohd Helmy; Riman, Ahmad Al’ Hafiz; Abdul Kadir, Herdawatie; Sanudin, Rahmat; Johari, Ayob; Mohd Sidek, Roslina; Ahmad, Noraziah (Springer, 2010)
This paper presents the design and development of Electronic pigeon hole integrated with GSM network to send a notification of any upcoming loaded. The electronic pigeon hole is able to send notification message via short message service (SMS) to the designated user if any new letter is placed in it. The innovation of the electronic pigeon hole could give immediate response for any urgent request for busy people. The system was developed by integrating a detection circuit to acknowledge the existing of new post items with the GSM modem to transmit SMS to specific user. It is found that the developed system is able to provide immediate notifications to intended users for further action.